Concealing a shiny facial skin appearance by an Aerogel‐based formula. In vitro and in vivo studies. (28th November 2017) - Cassin, G.; Diridollou, S.; Flament, F.; Adam, A. S.; Pierre, P.; Colomb, L.; Morancais, J. L.; Qiu, H.
Abstract: Objective: To explore, in vitro and in vivo, the potential interest of an Aerogel‐based formula, in concealing a naturally shiny facial skin. Methods: In vitro, various formulae and ingredients were applied as a thin film onto contrast plates and studied through measuring the shine induced following pump spraying of a mixture of oleic acid and mineral water as a sebum/sweat mix model. In such a test, an Aerogel ingredient led to very positive results. In vivo, two different formulae with various concentrations of Aerogel were randomly tested on half side of the face vs. bare side of Chinese women, under some provocative environmental conditions, known to enhance facial shine. These conditions comprised a normal activity under a hot and highly humid summer time followed – or not – by a hamam session. Both studies included comparative evaluations using a half‐face procedure (treated/untreated or vehicle). In the first case, evaluations were quantitatively carried out, whereas the second one was based on a quantitative self‐evaluations from standardized full‐face photographs Results: In vitro, the tested Aerogel, incorporated at 1% or 2% concentration in a common O/W cosmetic emulsion, shows an immediate light scattering effect, thereby masking shine. Such effect appears of much higher amplitude than that of two other tested particulate ingredients (Talc and Perlite). A noticeable remanence of anti‐shine effect was confirmed in vivo in extreme conditions. The latter was self‐perceived by all participants in the second study. This result is likely related to the super hydrophobic behaviour of the Aerogel. Conclusion: As cosmetic ingredient, this new Aerogel appears as a highly promising ingredient for concealing the facial skin shine, a source of complaint from many consumers living in hot and humid regions. Abstract : Half‐face appearance 6‐h post‐application of either the 1% or 2% Aerogel formula versus vehicle alone.